Management of speeding comparing two applied engineering measures - Ebrahim, Zuhair; Nikraz, Hamid (Polska Akademia Nauk * Komitet Inzynierii Produkcji, 2013)
The importance of safety comes from the responsibility towards protecting the vulnerable road users, who seem to be the victims in most road crashes. Thus, authorities tend to focus on reducing the travelling speed of the vehicles, whereas some road users may consider the move to interfere with mobility. In this study, a case study in Perth's two roads was conducted to compare two engineering treatments of speed reductions on these two busy shopping strips. The study aim is to illustrate the effect of using the electronic flashing signs rather than the standard signs in terms of speeding reduction and harm minimisation. Crash data were analysed and supported the safety benefits of the electronic flashing signs. Authorities have measured the reduction of the travelling speeds of vehicles and found it to be encouraging. There are clear, positive safety benefits from the study in terms of engineering and enforcement measures. © 2013, Versita. All rights reserved.